INTEGRATING CORPUS LINGUISTICS IN EFL CLASSROOMS AND DATA-DRIVEN LEARNING FOR LEXICAL ACCURACY - Elmirzayeva Maftuna Dusmurod qizi; Husanova Laylo Shuhratovna (Modern American Journals, 2025)
This article explores the integration of corpus linguistics and Data-Driven Learning (DDL) into EFL classrooms to enhance learners’ lexical accuracy. By analyzing real-life language use through learner-friendly corpora, students gain insights into word usage, collocations, and contextual appropriateness. The study investigates upper-intermediate learners’ experiences with tools such as COCA, BNC, and SkELL, comparing outcomes with traditional vocabulary instruction. Results suggest that corpus-based activities improve lexical awareness and promote independent learning. The article also discusses challenges faced by learners and offers practical recommendations for implementing DDL effectively in classroom settings.
Keywords: Corpus linguistics, Data-Driven Learning (DDL), lexical accuracy, EFL learners, collocation, vocabulary instruction, concordance tools